A theological study of “the enemies” in the Psalter and the Yorùbá worldview - Ogunkunle, Caleb (Stellenbosch Theological Journal, 2023)
The violent prayers in imprecatory Psalms have attracted serious criticism among Christians and Biblical scholars who find it difficult to reconcile the spirit of vengeance in the Psalms with the injunction of Jesus Christ that says, “Pray for your enemies and those who persecute you” (Mt 5:43-48). Biblical scholars have done profound research on imprecatory Psalms, but none of them has given significant attention to the activities of the enemies which motivated this present study. Therefore, this article examines the concept of enemies in the Psalter and the Yorùbá worldview to gain insight into the spiritual implications of dealing with enemies in each context. In addition to a review of the literature on the Psalter, a textual analysis of Psalms 35, 69, and 109 was carried out. Also, Yorùbá proverbs and pithy sayings lend credence to the Yorùbá perspective of the enemies. It was discovered that the enemies in each of the contexts were bent on destroying their perceived foes. Consequently, individuals in each cultural setting tried to be freed from the clutches of these enemies. The essay concludes that the Psalter and the Yorùbá worldview have brought different angles to the concept of enemies, which would help appreciate the complexities of enemies on a global scale. The article recommends that individuals should not give up in the face of challenges emanating from enemies and their activities.